Defining Extreme Sport: Conceptions and Misconceptions - Cohen, Rhonda; Baluch, Bahman; Duffy, Linda J. (Frontiers in Psychology, 2018)
One feature in how sport is defined is the distinction between extreme and non-extreme. BASE jumping is an example of an ‘extreme sport’ because it involves a high degree of ‘risk’, whilst swimming is classified as ‘non-extreme’ because the risks are minimal. This broad definition falls short of identifying the extent of risk and ignores the psychological, social-demographic and life style variables associated with engagement in each sport. Indeed the lack of consistency within the term ‘extreme sport’ means that those wishing to study this field are forced to create their own criteria as a starting point, often in a less than scientific approach. This review raises the key question of whether the definition of extreme sport is one of risk taking with a high chance of injury or death or if there are more to be considered. Furthermore do factors other than risk, i.e. psychological, socio-demographic and lifestyle, contribute to the defining features of extreme sports? The aim of this article is twofold: first to demonstrate how the term ‘extreme sport’ in scientific terms, has developed into a misnomer, misleading in the context of the sports it tends to encompass. Secondly, to propose a revised, more accurate definition of extreme sport, reflective of the activities it encompasses in the context of other non-mainstream sports. Based on this review it is argued that a new definition of an ‘extreme sport’ is one of “a competitive (comparison or self-evaluative) activity within which the participant is subjected to natural or unusual physical